Exploring the relation between language experience, verbal working memory and visual and verbal long-term memory - Motlhabane, Otsile (My University, 2016)
A comprehensive study has demonstrated that language experience provides cognitive benefits above the attainment of a second language (Bialystok, Craik, Green & Gollan, 2009) and thus it is purported that being a bi/multilingual stimulates memory and other executive functions (Jessner, 1999).The relation between language experience and verbal working memory and visual and verbal long-term memory was explored by assessing 30 healthy, young multilingual adults. The instruments that were used for this study are as follows: The Language Experience and Proficiency Questionnaire (LEAP-Q) which rated self-reported language experience/s, the Letter-Number Sequencing subtest from the WAIS-IV which assessed verbal working memory, the Visual Reproduction (VR) subtest from the WMS-IV which evaluated visual long-term memory and the Rey Auditory Verbal Learning Test (RAVLT) which measured verbal memory and learning. The results of the ANOVA statistics found that there was a correlation between language experience and verbal long-term memory (which was measured by utilising the RAVLT), but no links between language experience and verbal working memory and visual long-term memory were found. The results suggest that the language experience of young, multilingual adult South Africans is not related with verbal working memory and visual long-term memory.
Degree: MA in Psychology by Coursework and Research Report, 2016
Keywords: Memory (Psychological aspects); Second language acquisition--Research; Multilingualism--Psychological aspects